Tuning the electrical and optical properties of two dimensional materials - He, Z (2016)
The emergence of 2D materials inspires the pursuit of all-2D materials based devices which are predicted to outperform those with conventional architectures and materials. To achieve this goal, thorough understanding of the fundamental electrical and optical properties of 2D materials separately and the ability to manipulate these properties via external modulation methods are essential. Graphene can perform as transparent electrodes, yet suffering from its high sheet resistance. It was demonstrated that it can be greatly reduced via doping iron (III) chloride solution onto graphene film with high optical transmission at visible range if an optimal dopant solution concentration was employed. Doping with nanoscale spatial resolution was then achieved with the help of aberration-corrected transmission electron micro- scope, allowing in-situ observation of the atomic structures of doped regions, which possess unique properties predicted by DFT calculations. Transition metal dichalcogenides (TMDCs) can perform as active materials due to their sizeable bandgap. Therefore, the focus of this thesis then shifted to the investigation of WS2 . Three different methods were employed to alter the optical properties of WS2 . Firstly, the photoluminescence (PL) of WS2 presents layer dependent response towards lateral electric field, with PL quenching in monolayer and PL enhancement in bilayer. The results of temperature dependent PL measurement ruled out the joule heating effect. A possible mechanism based on the inter-valley electron transfer induced recombination pathways modification was then proposed.